Impact of mastectomy on the sexual and emotional life of women attended by a health service north of Minas Gerais - Patrick Leonardo Nogueira da Silva; Larissa Martins Silva; Mariley Simões de Souza; Carolina dos Reis Alves (Universidad de Alicante, 2018)
This study aims to understand the impact of mastectomy on the sexual and emotional life of women receiving care at a health facility in northern Minas Gerais. This is a descriptive, exploratory study with a qualitative approach, conducted with 12 women in the radiotherapy department of a hospital. We used a not structured interview for data collection. Data were recorded and fully transcribed for further categorization and analysis. Data processing was done through content analysis. It was evident that after radical mastectomy, sexual and emotional life of women is committed by both the physical effects of treatment, such as the psychosocial consequences, such as the construction of female identity, self-image and how to understand others the sighted. It is concluded that there are significant changes in the lives of these women, but the removal of the breast means the removal of a problem and the desire to be cured is greater than losing a breast.